Levothyroxine dosing post total thyroidectomy – the ideal equation?. (1st March 2022) - Oh, Soo; Rathod, Sneha; Ross, Elizabeth
Abstract: Aims: Levothyroxine (LT4) therapy is necessary post total thyroidectomy to suppress TSH for differentiated thyroid cancer (DTC) and euthyroidism for benign thyroid disorders. We aim to evaluate the accuracy of empirical LT4 regimens alongside existing formulas in literature and identify predictive variables for LT4 dosage. Methods: Retrospective study between January 2018 to February 2021 for all total thyroidectomies at UHNM. Total 50 cases identified from central database for each group (DTC vs benign). Data collected and analysed including patient demographics, diagnosis, LT4 regimens and thyroid function. Results: Most patients were started empirically on 125mcg/day LT4 (92% vs 90%, DTC vs benign). This led to 78% of DTC group and 82% of benign group being within 25mcg of the final LT4 regimen. For DTC thyroidectomies, comparing 125mcg/day versus recommended 2mcg/kg had an average error of -9.1% versus +26.1%. Correlation between Body Mass Index (BMI), Lean Body Mass (LBM) or Body Surface Area (BSA) to final LT4 was weak to moderate ( r =0.4 p=0.002, r =0.6 p=<0.001, r =0.6 p=<0.001). For benign thyroidectomies, comparing 125mcg/day to BNF dose 1.6mcg/kg and formulas in literature resulted in average error ranging between -1.9% to +27.1%. The best average error was +0.2% using the formula 1.5mcg/kg by Jin et al . No correlation was found between BMI, LBM or BSA with final LT4 regimens ( r =0.1 p=0.443, r =0.2 p=0.216, r =0.2 p=0.211). Conclusion: In our subset, empirical dosing at 125mcg gives reasonable estimate of final LT4 dose. BMI, LBM or BSA alone was not a consistent predictor for final LT4 dose. Further validation of predictive formulas is needed.